TRANSPARENT SOAP FORMULATION WITH VARIOUS LEVELS OF CONCENTRATION OF TEAK LEAF EXTRACT (TECTONA GRANDIS L.F.)AS ANTIBACTERIAL SOAP - Pranata, Chandra; Irwanto, Reno; .S, Aminah (Jurnal FARMASIMED (JFM), 2023)
The purpose of this study was to examine the organoleptic, homogeneity and antibacterial properties of transparent soap. The treatment used is; F1 (3% teak leaf extract), F2 (6% teak leaf extract), F3 (9% teak leaf extract), and F4 (12% teak leaf extract). The implementation of the research begins with product optimization in advance of the proportion of the use of raw material components. The results of the homogeneity test experiment showed that all formulas were homogeneous and in accordance with SNI standards, then the results of the water content obtained from each preparation proved to meet the requirements set by SNI ( Indonesian National Standard). The results of the pH measurements showed that at pH F0 it remained at 8. The results for measuring pH F1 showed results with a pH of 8. Meanwhile, pH F2 had a pH of 8. The last measurement for pH at pH F3 showed the same pH results as the other formula, namely at pH 8. So that F0, F1, F2, and F3 have the same pH, namely pH 8, where pH 8 is the pH of the positive control, namely soap on the market. Staphylococcus aureus with a concentration of 3% by 13 mm, 6% by 15 mm, 9% by 17 mm, 12% by 20 mm. The greater the concentration of teak leaf extract in transparent solid coir, the greater the inhibition of bacterial growth.